Ship Electric Propulsion Simulation System Reliability Evaluation Based on Improved D-S Expert Weight Calculation Method. (23rd June 2015) - Li, Bing; Gu, Guoliang; Xing, Bowen; Li, Lihong
Abstract : In order to have a better evaluation process to determine the experts weight in the evaluation process, this paper proposes a new expert weight calculation method. First of all to establish electric propulsion simulation evaluation system, use AHP method to calculate the initial weight principle of index. Then use the D-S to fuse the experts evaluation information, combined with the weight vector, structure of the expert weight objective function, and through the genetic algorithm to solve the expert weight size. According to the expert weight vector, calculate the final weight vector. Not only can it greatly make use of the experts information and analyze the similarity of information effectively but also it calculates the weight of each expert objectively. At the same time the evaluation subjective factors have been reduced by the adoption of this new method.